A Review on Swarna Kalpas Mentioned in Rasaratnasamucchaya (International Journal of Ayurveda and Pharma Research, 2021)
Rasasastra an independently originated science which became a significant part of Ayurveda deals with the pharmaceutics and therapeutic aspects of the metals and minerals. Rasaratna samucchaya is a well known Rasasastra textbook which describes both the aspects of various Rasaushadhis. A literature review on Swarna kalpas mentioned in Rasaratna samucchaya has been conducted here. The available data was classified and tabulated in the order of chapters. A total of 52 formulations were identified with presence of Swarna as an ingredient and among them, more number of formulations (10) were mentioned in Vajikarana adhyaya compared to other chapters.